2019
DOI: 10.1107/s2052252519004007
|View full text |Cite
|
Sign up to set email alerts
|

Competition between cubic and tetragonal phases in all-d-metal Heusler alloys, X 2−x Mn1+x V (X = Pd, Ni, Pt, Ag, Au, Ir, Co; x = 1, 0): a new potential direction of the Heusler family

Abstract: In this work, a series of all-d-metal Heusler alloys, X 2 − x Mn1 + x V (X = Pd, Ni, Pt, Ag, Au, Ir, Co; x; = 1, 0), were predicted by first principles. The series can be roughly divided into two categories: XMn2V (Mn-rich type) and X 2MnV (Mn-poor type). Using optimized structural analysis, it is shown that the ground state of these all-d-metal Heusler alloys does not fully meet the site-preference rule for classic full-Heusler alloys. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…It is found that the calculated total energy of Pd 2 CoAl in L2 1 -type structure is always smaller than in XA-type structure throughout the whole lattice variation range, which means the L2 1 -type structure is more energetically preferable and should be the ground state. This observation is in a good agreement with the general site preference rule found in other palladium-based Heusler compounds [32,34], i.e., since the Pd atom has more valence electrons than the Co atom, it is more electronegative and prefers the A and C sties. Thus, the L2 1 -type structure is formed for Pd2CoAl.…”
Section: Crystal Structure and Equilibrium Latticesupporting
confidence: 90%
See 1 more Smart Citation
“…It is found that the calculated total energy of Pd 2 CoAl in L2 1 -type structure is always smaller than in XA-type structure throughout the whole lattice variation range, which means the L2 1 -type structure is more energetically preferable and should be the ground state. This observation is in a good agreement with the general site preference rule found in other palladium-based Heusler compounds [32,34], i.e., since the Pd atom has more valence electrons than the Co atom, it is more electronegative and prefers the A and C sties. Thus, the L2 1 -type structure is formed for Pd2CoAl.…”
Section: Crystal Structure and Equilibrium Latticesupporting
confidence: 90%
“…However, several recent studies have found many Heusler materials have tetragonal structure as the ground state, e.g., Felser et al [29] found that Mn 3-x Fe x Ga and Mn 3-x Co x Ga have tetragonal structure over the whole range of compositions from experiment results, and then Faleev et al [30,31] performed an extensive investigation on the origin of the tetragonal ground state for 286 Heusler compounds by theoretical calculation, which shows 62% have tetragonal structure. More recently, Han et al [32,33] and Wu et al [34] studied the phase competition between cubic and tetragonal structures in a series of conventional Heusler compounds Pd 2 YZ (Y = Co, Fe, Mn; Z = B, Al, Ga, In, Tl, Si, Ge, Sn, Pb, P, As, Sb) and all-d-metal Heusler compounds X 2-x Mn 1+x V (X = Pd, Ni, Pt, Ag, Au, Ir, Co; x = 1, 0) and Zn 2 MMn (M = Ru, Rh, Pd, Os, Ir) and found that many of them also exhibit tetragonal phases, especially the most of Pd 2 Co-based Heusler alloys. Compared with the cubic structures, the tetragonal ones have several special properties, like large perpendicular magnetic anisotropy [35][36][37] and ferromagnetic shape memory behavior [38][39][40][41][42][43], which are very important for the development of spin-transfer torque magnetic random-access memory, ferromagnetic shape memory alloys and other spintronic applications [29,[44][45][46].…”
Section: Introductionmentioning
confidence: 97%
“…Based on the crystal structure obtained for CrB 2 , the dynamical stability of CrB 2 was examined based on the calculated phonon dispersion along the Γ–M–K–Γ–A–L–H–A paths (see Figure 1 c). Usually, if the system does not contain imaginary frequencies in the phonon dispersion, it can be regarded as having dynamic stability [ 49 , 50 , 51 ]. As shown in Figure 2 , the absence of imaginary frequencies in the first BZ reflects its dynamic stability.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the quaternary Heusler with formula XX 0 YZ has stoichiometric ratio of 1 : 1 : 1 : 1 and thus the name of equiatomic quaternary Heusler (EQH) is derived. 22,[48][49][50][51][52][53][54][55][56][57] Both experimental investigations and theoretical calculations have gradually began, e.g., Bainsla et al have prepared the equiatomic quaternary CoFeCrAl Heusler alloy with arc melting technique and found that it exhibits Y-type structure with only a very small amount of anti-site disorder and it has half metallicity with high spin polarization; 52 Paudel et al have theoretically studied the structural, magnetic, electronic and elastic properties for the LiMgPdSb-type EQH alloys CoFeZrZ (Z ¼ Ge, Sb, and Si) and examined their half metallic behaviour under different values of Hubbard correlation parameter U by using GGA+U method; 53 Rani et al have combined a theoretical and experimental study on the half metallic behaviour of EQH alloys CoRuMnGe and CoRuVZ (Z ¼ Al, Ga); 54 Wang et al and Hao et al have designed new EQH compounds ZrRhTiIn and TiZr-RuZ 49 (Z ¼ Al, Ga, In) from rst principle computations; 55 several other works focused on the rare-earth-element based EQH materials, like ScFeCrT (T ¼ Si, Ge), LuCoCrZ (Z ¼ Si, Ge), YCoCrZ (Z ¼ Si, Al, Ge, Ga), MCoVZ (M ¼ Lu, Y; Z ¼ Si, Ge) and they show better prospect for spintronic applications; 51,58,59 and Gao et al conducted a high-throughput screening for spin gapless semiconductors (SGSs) in EQH compounds aer Bainsla et al reported the SGS signature in EQH CoFeMnSi. 48,56,60 Compared with the ternary Heusler materials, the EQH compounds bring out several special advantages, like high composition exibility and better property tunability.…”
Section: Introductionmentioning
confidence: 99%